(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Currently, the head of the country is paying a lot of attention to the field of education. It is no coincidence that more than 60 percent of our state budget is allocated to education. We know that the future is in the hands of the youth. Taking this into account, our head of state considers the introduction of modern technologies into the field of education as one of the main tasks.Our opinion is also confirmed by the fact that there are no schools, academic lyceums, institutes, and universities in our country that have not yet received a modern computer. Modernization of the field of education in this way is a great help in raising the level of knowledge of pupils and students. These days, educational processes are creating wide conditions for learning foreign languages. In particular, great conditions are being created for this issue by our head of state. For this purpose, a number of decisions and laws were adopted on this issue.